Multinuclear magnetic resonance study on aluminium sec-butoxide chelated with ethyl acetoacetate in various amounts - Kurajica, Stanislav (Array, 2019)
Reactive aluminum alkoxide (ASB, aluminium sec-butoxide) was chelated using β-diketone (EAA, ethyl acetoacetate) in order to gain control over rapid hydrolysis in the course of the sol-gel process. Derived chelates were analysed using several NMR spectroscopic techniques: one-dimensional 1H, 13C, 27Al NMR and two-dimensional COSY, HSQC and DOSY. The NMR analysis enabled identification of the formed chelate species, as well as determination of their quantitative relationships. Several complexation products were observed: tris-chelated monomer, Al(EAA)3, bis-chelated dimmer, Al2(OnBu)4(EAA) 2, tris-chelated dimmer, Al2(OnBu)3(EAA)3, tetra-chelated dimmer, Al2(OnBu)2(EAA)4, and monochelated trimer, Al3(OnBu)8(EAA). Of the formed oligomer compounds, this is the first evidence of Al2(OR)3L3 in any alkoxide and β-ketoester or β-diketone combination. Aluminium sec-butoxide and ethyl acetoacetate complexes Al2(OnBu)4(EAA) 2 and Al2(OnBu)2(EAA)4 were also observed for the first time. With the increase of the EAA/ASB ratio the coordination of aluminium shifts towards six, whereas above the EAA/ASB ratio of 2.5 solely six-coordinated aluminium exists.